Dynamics of Multiculturalism in Indonesian Elementary Schools in the Global Landscape - Azhary, Luqman; Wasino, Wasino; Handoyo, Eko (Universitas Negeri Semarang, 2025)
This study aims to explore the dynamics of multicultural education at SD Mataram Semarang in a global context. The background of this study is based on the increasing need to teach multicultural values ​​in dealing with complex social situations in a diverse society such as Indonesia. The methodology used in the study consisted of observation, interviews with teachers and students, and analysis of documentation related to extracurricular activities. The results of the observations showed that SD Mataram has various extracurricular programs that integrate local and national cultures, which contribute to increasing students' understanding and appreciation of cultural differences. The results of the interviews indicated that teachers were very enthusiastic about implementing multicultural education despite facing several challenges, such as lack of adequate training. Documentation from school activities, such as cultural festivals and club activities, showed active participation of students in celebrating diversity. The important findings of this study emphasize the role of multicultural education as an effort to shape more tolerant and inclusive characters among students. This study is expected to contribute not only to educational policies at the local school of SD Mataram, but also to the practice of multicultural education more broadly in Indonesia and globally.